2012
DOI: 10.1364/ao.51.007262
|View full text |Cite
|
Sign up to set email alerts
|

Increase in laser beam resistance to random inhomogeneities of atmospheric permittivity with an optical vortex included in the beam structure

Abstract: The role of the vortical phase in the initial structure of the wave field of a laser beam propagating in the turbulent atmosphere in statistical regularities of beam wandering is studied. It is found that in the near diffraction zone the variances of wandering of the vortical beam and the fundamental Gaussian beam turns out to be identical, if the initial radius of the Gaussian beam is equal to the radius of the ring intensity distribution of the vortical beam. In the far diffraction zone, the vortical beam wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 14 publications
1
12
0
4
Order By: Relevance
“…3, which shows the calculated wandering of beams in the far diffraction zone behind the turbulent layer. Figures 2 and 3 demonstrate the expected behavior [17,20,21] of the beam wandering as a function of the turbulence intensity in the layer.…”
Section: Results Of Numerical Experiment: Variance Of Random Wanderingmentioning
confidence: 61%
See 1 more Smart Citation
“…3, which shows the calculated wandering of beams in the far diffraction zone behind the turbulent layer. Figures 2 and 3 demonstrate the expected behavior [17,20,21] of the beam wandering as a function of the turbulence intensity in the layer.…”
Section: Results Of Numerical Experiment: Variance Of Random Wanderingmentioning
confidence: 61%
“…However, these papers are mostly based on the Rytov method and do not cover vortex beams, for which the direct application of the Rytov method faces some problems [18,19]. To study the wandering of the Laguerre-Gaussian (LG) beam, we have used the semi-analytical approach and have shown that for weak and moderate turbulence this beam is more resistant to the effect of the turbulent atmosphere as compared to the fundamental Gaussian beam [20]. As a result of numerical simulation by the method of phase screens, we have found [21] that for the beam with the same initial intensity distribution as in the LG beam, but without helical phase, random displacements of centroid are more significant than those for the LG beam.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable effort has been devoted to the formulation of beam-wander variance for various types of optical beams [1][2][3][4][5][6]; the effect of the partial coherence of the source on the beam-wander variance was also studied by Berman et al [7], followed by Xiao and Voelz [8] and Yu et al [9]. The dynamics of beam wander are manifested in their temporal spectra.…”
mentioning
confidence: 99%
“…Ñòðîãîå ðåøåíèå ýòèõ óðàâíåíèé äëÿ ðàñïðîñòðàíåíèÿ ãàóññîâà ïó÷êà áûëî ïîëó÷åíî äëÿ ôóíêöèè êîãåðåíòíîñòè âòîðîãî ïîðÿäêà, à äëÿ ñòàòèñòè÷åñêèõ ìîìåíòîâ áîëåå âûñîêîãî ïîðÿäêà èçâåñòíû àñèìïòî-òè÷åñêèå ïðèáëèaeåíèÿ äëÿ ðåaeèìà ñëàáûõ è ñèëüíûõ ôëóêòóàöèé èíòåíñèâíîñòè. Äëÿ ñëó÷àÿ ïðîèçâîëüíîãî íà÷àëüíîãî ðàñïðåäåëåíèÿ îïòè÷åñêîãî ïîëÿ èñïîëüçóþò ðàçëè÷íûå ïðèáëèaeåíèÿ [12][13][14][15][16][17][18][19][20].…”
Section: ââåäåíèåunclassified